Interpretable machine learning models to predict survival in esophageal cancer: a study based on the SEER database and external validation in China - Tuersun, Abudouresuli; Abudoubari, Saimaitikari; Abudouwake, Abudoushalamu; Tuerdi, Huerxidan; Maimaitiyiming, Abulizi; Nijiati, Pahatijiang; Qiu, Ya; Wang, Jianquan (Frontiers in Physiology, 2025)
ObjectiveWe developed interpretable machine learning (ML) models to predict the overall survival (OS) of esophageal cancer patients. This approach aims to make our modeling results more interpretable and transparent.MethodsWe collected the clinicopathological information of esophageal cancer patients from the SEER database and divided them into training and validation sets at a ratio of 7:3. Meanwhile, we obtained an external validation cohort from the First People’s Hospital of Kashi in Xinjiang, China. Using LASSO and multivariate Cox regression analyses, we identified relevant risk factors and combined them to develop CoxPH and 6 ML models: Random Survival Forest (RSF), Gradient Boosting with Component Linear (GLMboost), decision tree (dt), boosting tree (bt), DeepSurv, and neural multi-task logistic regression (NMTLR). We evaluated the predictive performance of these ML models using the C-index, integral cumulative/dynamic AUC, integral Brier score, Kolmogorov-Smirnov (KS) test and Cramer-von Mises (CvM) test. For interpretability assessment, we employed three complementary methods: (1) time-dependent variable importance to quantify feature contribution across follow-up periods; (2) partial correlation survival plots to visualize individual variable effects; and (3) aggregated survival SHapley additive interpretation (SurvSHAP) plots with mean absolute deviation metrics to validate feature impact stability at both individual and population levels.ResultsThe final ML model consisted of 11 factors: grade, stage, T stage, N stage, M stage, radiotherapy, chemotherapy, bone metastasis, liver metastasis, lung metastasis, and age. Our predictive models demonstrate significant discriminative power; in particular, the NMTLR model performs best. For the training, validation, and external validation sets, the area under the curve (AUC) for one-, three-, and 5-year OS was higher than 0.81, and the integrated Brier score was consistently lower than 0.175. interpretability analyses confirmed consistent predictive logic: M stage, N stage, age, grade, bone metastases, liver metastases, lung metastases and radiotherapy were identified as the most influential predictors via quantifiable SurvSHAP values and time-dependent importance weights, with their effects visually validated through partial correlation survival curves.ConclusionThe NMTLR prognostic model is the most effective at predicting the OS of esophageal cancer patients. It helps physicians correctly assess patient survival and provides valuable information for diagnosis and prognosis evaluation.